Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Contextual Teaching and Learning (CTL) pada Materi Relasi dan Fungsi Kelas VIII - Lutfiani, Rini; Putri, Agustiany Dumeva; Ramury, Feli (Postulat : Jurnal Inovasi Pendidikan Matematika, 2025)
This research attempts to create LKPD-based instructional materials based on Contextual Teaching and Learning on Relation and Function that are workable, useful, and impact the learning outcomes of MTs Rahmatullah Mesuji Raya OKI Regency's class VIII pupils. Quantitative descriptive approach is used in this study. Using strategies for research and development. Analysis, design, development, implementation, and evaluation are the five steps of the ADDIE development model, which is followed in the development process. Questionnaires and tests were employed to collect data. To gather and analyze the data, test data analysis methods, practicality questionnaires, and validity questionnaires were employed. The results (1) MTs Rahmatullah Mesuji Raya Learner Worksheet (LKPD) on CTL-based relation and function material is qualitatively valid. The findings of validators from the Development stage, who evaluated the characteristics of language, construct, and content, confirmed the validity of the evaluation of this LKPD. (2) The CTL-based LKPD is considered very practical considering the developed relations and functions. This practicality was transferred to the large group trial based on the results of the learner response questionnaire at the small group trial implementation stage. (3) LKPD based on contextual teaching and learning (CTL) can influence the learning outcomes of students through the relationship and function-based approach. This is indicated by the learning outcomes of students who are included in the very good category with a completeness rate of 81.2% and a very good category.